The Effectiveness of Health Animations in Audiences With Different Health Literacy Levels: An Experimental Study - Meppelink, Corine S; van Weert, Julia CM; Haven, Carola J; Smit, Edith G (JMIR Publications, 2015)
BackgroundProcessing Web-based health information can be difficult, especially for people with low health literacy. Presenting health information in an audiovisual format, such as animation, is expected to improve understanding among low health literate audiences. ObjectiveThe aim of this paper is to investigate what features of spoken health animations improve information recall and attitudes and whether there are differences between health literacy groups. MethodsWe conducted an online experiment among 231 participants aged 55 years or older with either low or high health literacy. A 2 (spoken vs written text) x 2 (illustration vs animation) design was used. Participants were randomly exposed to one of the four experimental messages, all providing the same information on colorectal cancer screening. ResultsThe results showed that, among people with low health literacy, spoken messages about colorectal cancer screening improved recall (P=.03) and attitudes (P=.02) compared to written messages. Animations alone did not improve recall, but when combined with spoken text, they significantly improved recall in this group (P=.02). When exposed to spoken animations, people with low health literacy recalled the same amount of information as their high health literate counterparts (P=.12), whereas in all other conditions people with high health literacy recalled more information compared to low health literate individuals. For people with low health literacy, positive attitudes mediated the relationship between spoken text and the intention to have a colorectal cancer screening (b=.12; 95% CI 0.02-0.25). ConclusionsWe conclude that spoken animation is the best way to communicate complex health information to people with low health literacy. This format can even bridge the information processing gap between audiences with low and high health literacy as the recall differences between the two groups are eliminated. As animations do not negatively influence high health literate audiences, it is concluded that information adapted to audiences with low health literacy suits people with high health literacy as well.